2022
DOI: 10.1039/d2qo00938b
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced C–O bond cleavage for copper-catalyzed allenyl radical cyanation

Abstract: Selective activation and transformation of C-O bonds under mild conditons is of great significance in synthetic chemistry because of the widespread existence of carbon-oxygen single bond. In this work, allenyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The reaction was not restricted to allyl substrates, as propargyl electrophiles were also suitable coupling partners with L6 as the ligand, providing a wide range of difluoromethylated allenes with high efficiency and selectivity (Scheme ). Although extensive efforts have been made in the preparation of allenes, scarce examples of efficient synthesis of difluoromethylated allenes have been reported. , Given the synthetic versatility of allenes and the unique properties of the difluoromethyl group in medicinal chemistry, developing efficient methods to access these valuable fluorinated structures is of great interest. We found that the regioselectivity of the difluoromethylation could be controlled by the propargyl substrates: branched propargyl sulfonates provided “linear” products ( 6a – 6k ), while linear propargyl sulfonates or chlorides afforded “branched” allenes as the major products ( 7a – 7d ), thereby providing a synthetically versatile route to difluoromethylated allenes.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was not restricted to allyl substrates, as propargyl electrophiles were also suitable coupling partners with L6 as the ligand, providing a wide range of difluoromethylated allenes with high efficiency and selectivity (Scheme ). Although extensive efforts have been made in the preparation of allenes, scarce examples of efficient synthesis of difluoromethylated allenes have been reported. , Given the synthetic versatility of allenes and the unique properties of the difluoromethyl group in medicinal chemistry, developing efficient methods to access these valuable fluorinated structures is of great interest. We found that the regioselectivity of the difluoromethylation could be controlled by the propargyl substrates: branched propargyl sulfonates provided “linear” products ( 6a – 6k ), while linear propargyl sulfonates or chlorides afforded “branched” allenes as the major products ( 7a – 7d ), thereby providing a synthetically versatile route to difluoromethylated allenes.…”
Section: Resultsmentioning
confidence: 99%
“…Such a protocol for selective allene syntheses faces three challenges: (1) the more reactive CC bonds may cause undesired transformations such as radical cyclization that complicates the target reaction, (2) the selectivity issue of propargylic radicals vs. allenyl radicals to form either alkyne 7,12 or allene products, and (3) a matched trapping reagent. Allenenitriles could be prepared though the corresponding Wittig reaction, 13 S N 2′-type substitution of the in situ generated propargylic phosphates, 14 cross coupling of propargylic substrates, 6 i ,15 and difunctionalization of 1,3-enynes. 16 Herein, we wish to report our results on copper-catalyzed cyanation of non-activated propargylic C–H bonds, affording di- or tri-substituted allenenitriles bearing an attractive remote sulfonamide in decent yields with an excellent chemo- and regio-selectivity tolerating many synthetically versatile functionalities (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, this metallaphotoredox catalysis has received broad significance and empowered the exploration of a few new C–C and C–heteroatom bond-forming/cleavage protocols through C–H activation and cross-coupling reactions. 2,3 Each breakthrough reported in metallaphotoredox catalysis contributed to the green chemistry approaches such as up-grading efficiency, eco-compatibility and cost minimization. On the other hand, owing to the substantial examples of nitrogen-based heterocycles and building blocks found in the agrochemical, pharmaceutical, and materials science fields, the development of innovative methods to construct C–N bonds is of foremost importance.…”
Section: Introductionmentioning
confidence: 99%